QUALITY PROFILE OF DRIED FISH PRODUCED USING YTP-UNIB-2013 WITH VARIED DRYING TEMPERATURES - Iis Darniati; Yuwana Yuwana; Syafnil Syafnil (Jurnal Agroindustri, 2015)
Objectives of this research were 1) to determine fish drying time YTP-UNIB 2013 biomass dryer with four different temperatures; 2) to compare the resulted dry fishes to SNI Standards for fish; 3) to find the optimum drying temperature to produce dry fish with better fit to SNI standards.Utilizing “ Kaseh” fish (Opisthopterus tardoore) as experimental sample dryings with temperatures 30-40 oC, 40-50 oC, 50-60 oC and 60-70 oC, in term of drying time, resulted 10 hours, 8 hours, 6.5 hours and 5.5 hours respectively. From the TPC point of view, the dry fishes produced by these temperature ranges contained 1,16 x 106 kol/g, 1,0875 x 106 kol/g, 0,744 x 106 kol/g and 0,8975 x 106 kol/g. These dry fishes fitted respectively to 8.6, 8.8, 8.4 and 7.8 average organoleptical scores. The finding suggested that drying with 50-60 temperature ranges would be proper choice for drying fish with YTP-UNIB 2013 biomass dryer.Keywords :